Implementation of Pharmacy Executive Quality and Safety Walkrounds at a Tertiary Academic Medical Center. (April 2022) - Alsowaida, Yazed Saleh; Kovacevic, Mary P.; Belisle, Caryn; Cotugno, Michael C.; Cooley, Tom; Matta, Lina; Fanikos, John; Dell'Orfano, Heather
Background: Executive Quality and Safety WalkRounds (EWRs) is a tool that engages department leadership in discussion with the front-line employees to solicit feedback to improve quality and safety. The purpose of this study was to evaluate the impact of the implementation of pharmacy department specific EWRs on quality and safety at a tertiary academic medical center.Method: This was a single-center, retrospective analysis conducted at Brigham and Women's Hospital between November 2016 and November 2019. This study aimed to analyze the implementation of EWRs conducted every other month throughout various service areas and satellites of the pharmacy department. Data evaluated included the number of EWRs conducted, the specific areas visited, the total number of action items recommended by the staff, along with the total number of action items that were completed or remained in process.Results: During the study period, 17 visits were completed in 12 different BWH pharmacy sub-departments. A total of 98 operational, technological, and environmental action items were recommended by staff to improve quality and safety. Of the 98 action items documented, 95 (96.9%) were completed by time of our analysis.Conclusion: Pharmacy department EWRs are an important and systematic process of communication between the pharmacy leadership and frontline staff. Pharmacy department EWRs have resulted in safety and quality improvements at different levels in the pharmacy department. The EWRs program at the pharmacy department was effective in identifying and completing safety initiatives to improve the safety culture of the department.